Cardiovascular responses induced by acute video game boxing performance in healthy women - Souza, Luciano Moreira de; Annoni, Raquel; Abreu, Luis Carlos de; Valenti, Vitor Engrácia [UNESP]; Valenti, Erica E; Oliveira, Fernando R.; Raimundo, Rodrigo Daminello; Silva, Sidney B. (GN1 Sistemas e Publicacoes, 2014)
BACKGROUND: Previous studies suggested that some interactive video games induce cardiovascular responses. However, some different styles of video games have not been investigated. OBJECTIVE: We aimed to evaluate cardiovascular responses induced by video game boxing performance in healthy women. METHOD: We evaluated ten female sedentary volunteers, aged 20.9 ± 1.4 years, weight 58.7 ± 8.0 kg, height 163.2 ± 5.4cm. All subjects were weighed and measured. Their heart rate, blood pressure and lactate levels were recorded before and after video game performance. The volunteers played a Sony video game (Nintendo® Wii) by using the boxing method, in which all volunteers played for 10 minutes without interruption. At the end of the game the volunteers were reassessed using the same parameters mentioned above. RESULTS: At the end of the video game boxing performance we observed highly significant increases of lactate production (p < 0.0035) and the double product (heart rate vs. systolic blood pressure) was also higher (p < 0.0001). Both parameters indicate that the performance increased demands of the cardiovascular system. CONCLUSION: We conclude that a ten-minute video game boxing performance induces cardiovascular responses similar to aerobic exercise. This may be a practical form of exercise, but care should be exercised concerning subjects with cardiovascular disorders.

BACKGROUND: Estudos anteriores sugerem que certos jogos de vídeo interativos induzem respostas cardiovasculares. No entanto, alguns estilos diferentes de jogos de vídeo nao foram investigados. OBJETIVO: Nosso objetivo foi avaliar as respostas cardiovasculares induzidas pelo video game desempenho boxe em mulheres saudáveis. MÉTODO: Foram avaliadas dez voluntárias sedentárias do sexo feminino, com idades de 20,9 ± 1,4 anos, peso 58,7 ± 8,0 kg, estatura 163,2 ± 5,4 cm. Todas foram pesadas e medidas. Suas frequências cardíacas, pressões arteriais e níveis de lactato foram registrados antes e depois de um jogo em vídeo game. As voluntárias jogaram um jogo de vídeo Sony (Nintendo ® Wii) usando a modalidade boxe, na qual todas jogaram por 10minutos ininterruptos. No final do jogo, as voluntárias foram reavaliadas utilizando os mesmos parâmetros mencionados acima. RESULTADOS: Ao final da performance de vídeo game boxe observamos aumentos altamente significativos de produção de lactato (p < 0.0035) e do duplo produto (frequência cardíaca versus pressão arterial sistólica) também foi maior (p < 0.0001). Ambos os parâmetros indicam que o desempenho aumentou a demanda de trabalho do sistema cardiovascular. CONCLUSÃO: Concluímos que uma performance de jogo de vídeo de boxe de dez minutos induz respostas cardiovasculares similares aos exercícios aeróbicos. Esta pode ser uma forma prática de exercício, mas cuidado deve ser exercido em relação a indivíduos com doenças cardiovasculares.